Sensitivity of resolved convection to ocean and land surfaces in the Tropical Atlantic and Amazon Basin - Paccini Peña, Laura Giulianna (2022)
Descargue el texto completo en el repositorio institucional de la Universität Hamburg: http://hdl.handle.net/21.11116/0000-0009-F864-F